4 married couples among 24 UMP staff selected for Dhuyufurrahman - Siti Nur Azwin, Zulkapri (UMPSA, 2023)
PEKAN, May 25, 2023 - A total of 24 staff members from Universiti Malaysia Pahang (UMP) will be performing the Hajj pilgrimage after receiving offers to fulfill the fifth pillar of Islam this year.